2008
DOI: 10.1109/tbc.2008.919012
|View full text |Cite
|
Sign up to set email alerts
|

Region of Interest-Based Adaptive Multimedia Streaming Scheme

Abstract: Abstract-Adaptive multimedia streaming aims at adjusting the transmitted content based on the available bandwidth such as losses that often severely affect the end-user perceived quality are minimised and consequently the transmission quality increases. Current solutions affect equally the whole viewing area of the multimedia frames, despite research showing that there are regions on which the viewers are more interested in than on others. This paper presents a novel region of interest-based adaptive scheme (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…In the face of challenging network conditions during real-time video streaming, UEP strategies [4,5,6] protect visually important (salient) regions more heavily. An often overlooked question in these works is how to conceal missing blocks in the less important regions when packet losses do occur?…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the face of challenging network conditions during real-time video streaming, UEP strategies [4,5,6] protect visually important (salient) regions more heavily. An often overlooked question in these works is how to conceal missing blocks in the less important regions when packet losses do occur?…”
Section: Related Workmentioning
confidence: 99%
“…Under these practical constraints, it is very difficult to guarantee error-free delivery of the entire video from sender to receiver in a timely manner. Many previous works [4,5,6] employed the pro-active methodology of unequal error protection (UEP) of video data, where important packets are protected more heavily (e.g., using stronger Forward Error Correction (FEC) codes). Typically, more important packets contain viewer's probable Regions-of-Interest (ROI) [7] in a video frame, or regions with higher visual saliency [8]-where viewers most likely will focus their visual attention.…”
Section: Introductionmentioning
confidence: 99%
“…Objective VQA metrics are wildly employed for assessing the video quality in both prototype-based [12] and simulationbased solutions [13]. Relative to the presence of the original reference video stream unaffected by the factors under test, the existing objective VQA metrics can be classified in: noreference (NR), reduced-reference (RR) and full-reference (FR) metrics [7].…”
Section: B Objective Vqa Metricsmentioning
confidence: 99%
“…In Engelke and Zepernick's study (2009), the result from image quality assessment showed that subjects were more sensitive to the image quality distortion in the ROI area than that in the background. According to Muntean et al (2008), by blurring the background and decreasing its saturation but increasing that of the foreground, better visibility could be achieved on mobile devices; and marginal background changes could reduce the video bitrate. Other studies (Knoche, Papaleo, Sasse & Vanelli-Coralli, 2007;Song, Tjondronegoro, Wang, et al, 2010) revealed that properly zooming the ROI or enhancing the quality of ROI based on the shot type of video content could efficiently improve the overall UX on a mobile device in a low bitrate condition.…”
Section: Optimizing User Experience Of Mobile Videomentioning
confidence: 99%